Effect of particle packing in the durability of high performance concretes - Ferreira, F.; Castro, A. (Revista Ingeniería de Construcción, 2016)
Due to the high aggressiveness in which the concrete structures are exposed, many researches have been developed in this area and search for materials with superior mechanical performance and durability has been the target of the researchers of concrete technology. Therefore, concrete obtained from the microstructure engineering are needed. Being composites made of fine grain particles and a low water/binder ratio, these materials have dense matrix by optimizing the packing of granular materials. Thus, this paper uses the concept of particles packing in the design of special concretes, analyzing the durability of these materials by determining the water absorption by immersion and by capillary, and chloride ion penetration. The properties of concrete designed based on this concept are compared to high performance concrete designed from conventional methodology, indicating superior properties in terms of durability.